PERSEPSI PENGGUNA TERHADAP KEMPEN BUY MUSLIM FIRST (‘BMF’), LOGO HALAL DAN LOGO ZAKAT PERNIAGAAN: KAJIAN DI SELANGOR: Consumers’ Perception towards Buy Muslim First (‘BMF’) Campaign, Halal Logo and Corporate Zakah Logo: A Study in Selangor - Wahid, Hairunnizam; Muhammad Zailani, Dhiyaul Aqif; Shhadan, Muhammad Azizi (Jurnal Syariah, 2022)
Corporate zakah collection in Selangor is still low compared to income zakah collection, although the amount of zakah collection has increased from year to year in tandem with the increase of Muslim entrepreneurs in Selangor. Situations like this affect the distribution of zakah by the Lembaga Zakat Selangor (LZS) as a whole, therefore causing some asnaf to not receive their distribution. The question posed here is whether the implementation of the Buy Muslim First (BMF) campaign, as well as the creation of awards in the form of certain logos to Muslim entrepreneurs who pay corporate zakah consistently can overcome this issue. This study aims to measure consumers’ perception of the BMF campaign as their perspective can in turn affect Muslim entrepreneurial companies as well as the Islamic economy. The analysis was done by testing several factors including price, income, the halal logo by JAKIM, halal logo(s) besides JAKIM’s logo, the business zakah logo and corporate social responsibility (CSR) factors. This study was conducted by distributing online questionnaire forms randomly (online survey) to 207 consumers in the Gombak and Hulu Langat districts of Selangor. Positive feedback was received on both the implementation of the BMF campaign and also the idea of ​​creating a business zakah logo. The results show that consumers are interested in prioritising Muslim products and agreed that the BMF campaign should be implemented and continued in Malaysia. This perception will affect the spirit of Muslim entrepreneurs who want to open and grow their businesses. The study also found that the business zakah logo variable and the existing company CSR variable were significantly related.